(untitled) (Universal International Scientific Journal, 2026)
This article examines the methods of organizing the training process for young skiers in triple jump at the initial training stage (11-12 years old). The physiological characteristics of adolescents, the use of G.V. Raschupkin’s methodology for forming the basics of jumping technique, and the effectiveness of special exercise complexes were analyzed. The main focus is on forming the rhythm of jumping and preparing the musculoskeletal system for specific loads